Optimization of 1,2,4‐butanetriol production from xylose in Saccharomyces cerevisiae by metabolic engineering of NADH/NADPH balance - Yukawa, Takahiro; Bamba, Takahiro; Guirimand, Gregory; Matsuda, Mami; Hasunuma, Tomohisa; Kondo, Akihiko (Biotechnology and bioengineering, 2021)
1,2,4‐Butanetriol (BT) is used as a precursor for the synthesis of various pharmaceuticals and the energetic plasticizer 1,2,4‐butanetriol trinitrate. In Saccharomyces cerevisiae, BT is biosynthesized from xylose via heterologous four enzymatic reactions catalyzed by xylose dehydrogenase, xylonate dehydratase, 2‐ketoacid decarboxylase, and alcohol dehydrogenase. We here aimed to improve the BT yield in S. cerevisiae by genetic engineering. First, the amount of the key intermediate 2‐keto‐3‐deoxy‐xylonate as described previously was successfully reduced in 41% by multiple integrations of Lactococcus lactis 2‐ketoacid decarboxylase gene kdcA into the yeast genome. Since the heterologous BT synthetic pathway is independent of yeast native metabolism, this manipulation has led to NADH/NADPH imbalance and deficiency during BT production. Overexpression of the NADH kinase POS5Δ17 lacking the mitochondrial targeting sequence to relieve NADH/NADPH imbalance resulted in the BT titer of 2.2 g/L (31% molar yield). Feeding low concentrations of glucose and xylose to support the supply of NADH resulted in BT titer of 6.6 g/L with (57% molar yield). Collectively, improving the NADH/NADPH ratio and supply from glucose are essential for the construction of a xylose pathway, such as the BT synthetic pathway, independent of native yeast metabolism. The NADPH regeneration strategy improved 1,2,4‐butanetriol production from xylose in yeast Saccharomyces cerevisiae. We revealed the integrating the 1,2,4‐butanetriol synthetic pathway strain induced the NADPH depletion. The overexpression of NADH kinase POS5△17 increased up to 2.2 g/L with a molar yield 33%. Sequential supply of glucose relieved the xylonate accumulation is major byproduct and BT production reached at 6.6 g/L after 144 h fermentation.